Indian-Israeli defence cooperation : the elusive strategic partnership - Bitzinger, Richard A. (2013)
Indian-Israeli defence cooperation is mainly based on Israeli arms sales to India, which are increasingly critical in military and economic terms, to both countries. However much Israel might like to expand this cooperation into a larger strategic partnership, India appears content with keeping this relationship limited and tactical.